SISTEM ORGANISASI SOSIAL DAN KEMASYARAKATAN SUKU BADUY - Eti Susanti; Sapriya; Supriatna, Encep (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Baduy community, located in Lebak Regency, Banten Province, Indonesia, represents an indigenous group that has preserved ancestral traditions amidst modernization. This article explores the social organization system of the Baduy community, including its hierarchical structure, customary norms, leadership roles, and interactions with the outside world. The social structure, led by the Puun as the spiritual leader and the Jaro as the administrative manager, is central to the community's continuity. Customary norms, known as "pikukuh," regulate all aspects of life, from social relations to environmental conservation. Despite facing modernization challenges, the Baduy community, particularly the Outer Baduy, demonstrates adaptability without losing cultural identity. This article adopts a descriptive approach, referring to recent literature and research, to provide a comprehensive understanding of the harmony between tradition, spirituality, and ecological sustainability in the Baduy community. The study highlights the Baduy community as a model of how traditions and local values can serve as a foundation for sustainable community management in the modern era.